Elemental composition of illicia and otoliths and their potential application to age validation in white anglerfish (Lophius piscatorius linnaeus, 1758). (31st October 2021) - Brophy, Deirdre; Pérez-Mayol, Sílvia; Duncan, Roxanne; Hüssy, Karin; Geffen, Audrey J.; Gerritsen, Hans D.; Villanueva, Maria Ching; Morales-Nin, Beatriz
Abstract: The incorporation of trace elements into the calcified structures of fish can vary seasonally. Interpretation of these seasonal signals can provide information about fish age. This approach offers great promise for objectively estimating age and corroborating other methods of age estimation for fish stock assessment. This study investigated seasonal variation in trace element composition of otoliths and illicia from white anglerfish ( Lophius piscatorius L.), a species that is very difficult to age using visual interpretation of growth bands in their calcified structures. A suite of trace elements (Na, Mg, Zn, Sr, Ba in illicia and Na, Mg, K, Sr, Ba in otoliths) was measured with LA-ICPMS using discrete ablations and continuous line scans. A method is presented to obtain reliable measurements of microchemical composition from illicia. Variation in elemental concentrations at the edge of the illicium was primarily related to fish length and no differences were detected between fish collected at different times of the year. In otoliths, Sr concentrations at the edge (0–100 μm) were highest in anglerfish collected during wintertime (quarter 1). Seasonal differences in Sr were statistically significant but small; a larger proportion of the explained variance was attributed to length and individual variability. Nonetheless, the seasonal pattern was consistently detected across all size classes, indicating that the analysis of cycles in otolith Sr could potentially provide a tool to support age estimation in white anglerfish. Highlights: A methodology is presented for analysing trace elements in illicia. Strontium concentrations in the otoliths of Lophius piscatorius show seasonal variation. Otolith microchemistry techniques could be used for age validation in Lophius piscatorius .